PENGARUH LABA AKUNTANSI LABA TUNAI DAN DIVIDEN KAS TERHADAP NILAI PERUSAHAAN (Studi pada Bank Umum yang Terdaftar di Bursa Efek Indonesia Periode 2016 – 2018) - Yubiharto Yubiharto (Sekolah Tinggi Ilmu Ekonomi Tamansiswa Banjarnegara, 2020)
ABSTRACT Companies can be assessed from the ability to generate profits, maintain investment value, and the company's ability to cope with company expenses that can be seen from the company's financial statements. Ideally banking company sector always experiences profits and always distributes dividends to shareholders, but the reality that banking sector companies are always fluctuative so there are some banks that do showed not distribute their dividends, and bank profits are also unstable. The purpose of this study was to determine the effect of accounting profit, cash profit, and cash dividend on the value of the company, From the analysis it was found that partially Accounting Profit, had no effect on firm value. Furthermore, cash profit, has a positive effect on company value. And the last partially Cash Dividend has a positive effect on company value. Accounting Profit, Cash Profit, and Cash Dividend simultaneously have an effect of 68.7%. and can be further developed with other variables that are not in this study.